Elementos subjetivos para la procedencia de la prisión preventiva. - Rodríguez Armijos, Carlos Alfredo (2015)
The importance and significance of socio-legal problem which results in the difficulty of accurately establish the "SUBJECTIVE ELEMENTS FOR THE ORIGIN OF THE PRISON PREVENTIVE" is of particular interest at present, therefore, the exceptionality and the restrictive nature of the remand, are constitutional safeguards that far from being ignored by judges and prosecutors when deciding to temporarily deprive a person of liberty, should be the subject of extensive analysis taking into account the facts of each case. In this regard, it is noteworthy that the current Constitution of the Republic of Ecuador, imperatively states in its Art. 77 paragraphs 1 and 11, the way it should be considered the exclusive injunction of freedom, so that through this work, is to illustrate what I mean about the realization of this principle taking as reference the constitutional system and its application in practice, highlighting the legal insufficiency contained in the above Adjective Criminal law and the current Penal Code of Integral, this in order to form a real perspective of what is the application of preventive detention in Ecuador, and thus propose a number of possible solutions to effectively meet the exceptional nature of this measure. That's why my research work is focused on addressing regarding establishment of the subjective elements that judges should take into account when issuing this precautionary measure personal, just that called principle of exceptionality of pretrial detention, which according to their subjective dimension should be understood the same as a program to banish the general application of the institute and invest the jurisdictional criterion postulate.